The process of innovation : a study of companies in Canada, the United States and the United Kingdom - Isherwood, Nuala Swords; British-North American Committee (United Kingdom : British-North American Committee, 1984)
Concern with industrial innovation and its role in competitiveness is now widespread. This study, reflecting this concern, is of the process of innovation in the UK and North America. It provides a micro-economic picture of innovative activity in a selection of companies in different industrial sectors in three countries, and follows up the 1981 British-North America Committee work on innovation by Kerry Schott.
Includes bibliographical references.
hza 25/07/2018
Loans
Keywords: Industrial management; Innovation-industry; Industry- innovation; United States